INDIGENOUS COUNSELING: KARAKTERISTIK SPIRITUAL DALAM TRADISI ROBO-ROBO PADA MASYARAKAT KECAMATAN SUNGAI KAKAP, KALIMANTAN BARAT - Saripaini Saripaini (Jurnal Studi Agama dan Masyarakat, 2021)
The robo-robo tradition is a traditional ritual carried out by the Sungai Kakap people as an effort to resist danger. This study explored to describe and identify the characteristics of people spirituality in the process of providing assistance through local community traditions. This research was a qualitative research using descriptive method. Data was collected by observing people’s life in the field and interviews. The result revealed that: 1) amongst their existence as human, they had an awareness of the need for the God's help. 2) close to nature and living environment. 3) had close relationships amongst people, social values such as the value of togetherness, the value of sharing and respect, and the value of kinship. 4) The relationship with God in the robo-robo tradition was divided into three groups, namely: first, religious people had faith in Allah SWT, and did not want to involve themselves in the robo-robo tradition. Generally, this group considered this custom to be a deviation in religion. Second, they had faith in Allah SWT, were involved in cultural celebrations but did not believe in the belief traditions developed in these celebrations. Third, they had faith in Allah SWT but also they had faith in other supernatural beings (soul / ancestral soul).